Morphology and Allometry of Juvenile Açaí Palms Under Cultivation Conditions in Central Amazonia - Jhon Paul Mathews Delgado; Raimundo Nonato Vieira da Cunha; Ronaldo Ribeiro de Morais; Maria Teresa Gomes Lopes; Santiago Linorio Ferreyra Ramos; Maria do Rosário Lobato Rodrigues; Nathalia Maíra Cabral de Medeiros; Carlos Henrique Salvino Gadelha Meneses; Edson Barcelos; Ricardo Lopes (Horticulturae)
Two Amazonian species of açaí palm trees (Euterpe oleracea and Euterpe precatoria) are exploited in the commercial production of açaí pulp or juice. While E. oleracea benefits from developed cultivation technologies, E. precatoria lacks such advancements. Studies on the morphology and development of açaí palms under cultivation conditions can contribute to increasing the productivity of the species. The aim of this study was to carry out morphological characterization, assess growth and development in the juvenile phase of the plants, and obtain allometric models for E. precatoria and E. oleracea. Evaluations were conducted between 44 and 48 months post-planting. Allometric equations were formulated to accurately estimate leaf area. The results showed that E. oleracea begins reproduction earlier and exhibits greater growth in stem dimensions and leaf areas compared to E. precatoria, indicating that E. precatoria can be cultivated at higher planting densities. Allometric models, based on leaf length and width, effectively predicted individual leaf areas for both species, demonstrating their utility in optimizing cultivation strategies.